Transient analysis of a piezoelectric-orthotropic laminate weakened by multiple embedded and interface cracks under impact loads. (February 2021) - Ayatollahi, M.; Milan, A.G.; Mirzania, P.
Highlights: Transient analysis of multiple cracks in a piezoelectric layer bonded to an orthotropic layer is studied. Dislocation densities are employed to determine field intensity factors for multiple cracks. The formulation is capable of analyzing multiple interfacial and embedded cracks with arbitrary arrangement. Abstract: The transient response of a piezoelectric layer bonded to an orthotropic layer under anti-plane mechanical and in-plane electrical impacts is investigated in this paper. The problem consist of two parts. In the first part, the analysis is based on the stress and electric displacement fields caused by electro-elastic dislocation in the piezoelectric layer, while the second part consist of the interfacial crack formulation by introducing the dislocation situated at the interface of two bonded layers. For both problems, the dislocation solution are obtained utilizing Fourier and Laplace transforms. These solutions lead naturally to singular integral equations for dislocation density functions in the both cases of embedded and interface cracks. The integral equations are solved numerically to obtain dislocation density functions on the surface of crack, which are used to calculate dynamic field intensity factors.